2016
DOI: 10.1097/rlu.0000000000001148
|View full text |Cite
|
Sign up to set email alerts
|

PSMA Expression in Papillary Thyroid Carcinoma

Abstract: Aim: PSMA (prostate-specific membrane antigen) is physiologically expressed in normal prostate tissue and over expressed in prostate cancer cells, therefore constituting a potential target for antibody-based radioligand therapy. Very recent imaging findings reported PSMA-PET/CT uptake in various thyroid lesions. We were therefore encouraged to systematically analyse PSMA expression in different benign and malignant thyroid lesions. Methods: Immunohistochemistry was used to detect PSMA expression in 101 thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…51%). Several publications reported about efficiency of 68 Ga-PSMA PET/CT in recognition of various RAI-resistant thyroid cancers, including PTC, FTC, and PDTC 27, 28, 33 . 18 F-FDG PET/CT is one of the most sensitive imaging modalities currently used in patients with RAI-refractory thyroid cancer 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51%). Several publications reported about efficiency of 68 Ga-PSMA PET/CT in recognition of various RAI-resistant thyroid cancers, including PTC, FTC, and PDTC 27, 28, 33 . 18 F-FDG PET/CT is one of the most sensitive imaging modalities currently used in patients with RAI-refractory thyroid cancer 30 .…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG PET/CT is one of the most sensitive imaging modalities currently used in patients with RAI-refractory thyroid cancer 30 . Preliminary clinical reports found that 68 Ga-PSMA imaging might have benefit over 18 F-FDG PET/CT, because it tends to detect more metastatic RAI-resistant foci, and was more effective in recognition of brain lesions 27, 33 . Similar results were also observed in prostate cancer, where PSMA PET/CT appeared more sensitive than conventional 18 F-FCH PET/CT 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the patients show poor and/or short-lived responses to systemic chemotherapies only, a problem that might at least in part be due to an ineffective drug delivery to pancreatic cancer cells [ 4 , 25 ]. PSMA expression in tumor-associated neovasculature has been described in a variety of solid tumors and is suggested to be involved in (neo)angiogenetic processes [ 10 – 15 ]. Therefore, the aim of this study was to analyze PSMA expression patterns in PDAC and to evaluate a possible correlation between PSMA expression, microvascular density, and response to Gemcitabine treatment in a cohort of 81 patients with histologically confirmed PDAC under palliative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been shown that PSMA is also expressed in the endothelium of tumor-associated neovasculature of breast, lung, thyroid, and urothelial cancer, where its enzymatic activity may be involved in malignancy-driven neoangiogenesis [ 10 – 15 ]. PSMA might in fact act as part of an autoregulatory loop involving β 1-integrin and p21-activated kinase 1 (PAK1) and facilitate endothelial cell invasion through the extracellular matrix (ECM) by interacting with the cytoskeleton via integrin signaling and actin-binding protein Filamin A [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…[78] PSMA uptake is also seen in both benign[9] and malignant neoplasms of thyroid. [101112] Although rare, metastatic spread to the thyroid gland from primary PCa has been reported in the past. [1314] In this patient, metastases to the thyroid was a distinct possibility in view of widespread metastatic disease not observed in this case.…”
Section: Discussionmentioning
confidence: 99%